English Teachers’ Attitudes and Pedagogical Beliefs: Basis for Designing Project SMART in Rural Public High Schools - Quiben, Racquel D.; Nebrida, Alan P. (Future Science / FSH-PH Publications, 2025)
This research examined the attitudes and pedagogical beliefs of secondary English teachers in Kayapa, Nueva Vizcaya, to inform the creation of a Learning and Development Program. The study used a descriptive-correlational quantitative methodology with complete enumeration, including all 30 English instructors from seven public secondary schools throughout the 2024–2025 academic year. Validated survey instruments were used, and results were evaluated by descriptive statistics and Pearson correlation. Findings revealed that educators often had favorable attitudes about English instruction, particularly with their dedication to teaching, job satisfaction, aspirations for professional growth, technical proficiency, and views on remuneration. Moreover, respondents demonstrated robust pedagogical attitudes across six essential dimensions: organizational practices, effective lesson delivery, classroom management and discipline, positive student involvement, successful assessment procedures, and commitment to ethical teaching standards. Statistical investigation validated a substantial positive association between educators' attitudes and their educational convictions. This indicates that the enhancement of one construct may concurrently elevate the other, highlighting the connection between attitude and instructional practice. Considering these results, a Learning and Development Program named Project SMART (Seminar-Workshop for Advancing Reflective Teaching) was established. The program seeks to enhance and maintain teachers' positive dispositions and robust pedagogical foundations by emphasizing technology integration, fostering professional development, and advocating ethical, learner-centered methodologies. This research highlights the essential importance of ongoing professional development in enhancing English teaching and elevating educational results, especially in rural public-school settings.